Moderate Differences in Feeding Diets Largely Affect Motivation and Spatial Cognition in Adult and Aged but Less in Young Male Rats - Maliković, Jovana; Feyissa, Daniel D.; Hussein, Ahmed M.; Höger, Harald; Lubec, Gert; Korz, Volker (Frontiers in Aging Neuroscience, 2018)
Nutrition can have significant effects on behavior and cognitive processes. Most of the studies related to this use extremely modified diets, such as high fat contents or the exclusion of distinct components needed for normal development and bodily homeostasis. Here we report significant effects of diets with moderate differences in compositions on food rewarded spatial learning in young (3–4 months), adult (6–7 months), and aged (17–18 months) rats. Young rats fed with a lower energy diet showed better performance only during aquisition of the spatial task when compared to rats fed with a standard diet. Adult rats (6–7 months) fed with a standard diet performed less well in the spatial learning task, than rats fed with lower energy diet. Aged rats fed with a lower energy diet (from 13 to 18 months of age) performed better during all training phases, as in a previous test when they were adult and fed with a standard diet. This difference could only be partly explained by lower motivation to search for food in the first test. Correspondingly, the variability of individual performance was significantly higher and increased over trials in adult rats fed with the standard diet as compared to adult rats fed with lower energy diet. Thus, moderate changes in feeding diets have large effects on motivation and cognition in elderly and less in young rats in a food rewarded spatial learning task. Therefore, nutrition effects upon food rewarded spatial learning and memory should be considered especially in aging studies.